Misadventures of a Civil War submarine : iron, guns, and pearls - Delgado, James P. (Ed Rachal Foundation nautical archaeology series., 2012)
In 2001, while vacationing on Panama's Pacific coast, maritime archaeologist James P. Delgado came upon the hulk of a mysterious iron vessel, revealed by the ebbing tides in a small cove at Isla San Telmo. Local inquiries proved inconclusive: the wreck was described as everything from a sunken Japanese ""suicide"" submarine from World War II to a poison-laden ""craft of death"" that was responsible for the ruin of the pearl beds, decades before. His professional interest fully aroused, Delgado would go on to learn that the wreck was the remains of one of the first successfu